KNOWLEDGE AND ASSOCIATED FACTORS FOR USE OF CONTRACEPTIVES AMONG MARRIED WOMEN OF WEST BENGAL, INDIA - Mondal, Moumita (International Journal of Research -GRANTHAALAYAH, 2024)
Use of contraceptive and family planning methods are help in fertility pattern and also helps to improve reproductive health. It is important to have proper knowledge about the contraceptives and identified the associated factor for the use of contraceptives by the married women. A study was conducted to assess the knowledge and the associated factor for the use of contraceptives among married women in the selected rural community of West Bengal. Non-probability purposive technique was used to collect data from 162 married women residing at the selected rural community. It was collected by using structured knowledge questionnaire and structured questionnaire for identify associated factor. The study revealed that 16.67% married women’s had poor knowledge, 12.34% married women’s had good knowledge. It observed that 48.76% married women belonged to the married life of 5-10 years. 72.22 % married women got contraceptives from Subcenter.38.89 % married women used Oral contraceptives pill.83.34 % married women’s were using contraceptives by couple choice.74.70 % married women’s advice taken from Health worker.42.85 % married women used Oral contraceptives pill because of Decision of couple.92.60 % women used Condoms because of because of Decision of couple.65.62% women used Injectables because of easily available .52.5 % married women used CU-T because of easily available. There was statistically significant association between knowledge of contraceptives and their demographic variables like, the religion, marital age.